The effect of specialised training on police performance through human-technology capability in Abu Dhabi - Abboud Aiyammahi, Ali Khameis Ali (2024)
In recent times, the effectiveness of police in upholding political stability and ensuring public safety has become a critical global concern, including in the United Arab Emirates (UAE). It has been reported that in Abu Dhabi, the capital of the UAE, the performance of the police forces has been subpar, impacting their ability to combat crime effectively and maintain community safety for residents. As a result of these challenges, they recognize the imperative of modernizing its policing strategies to address evolving crime dynamics and technological advancements. Against this backdrop, this study aims to explore the intricate relationships between specialised police training programs, human-technology capabilities, and police performance in Abu Dhabi, UAE. In general, the study investigates the significant potentials of human-technology capability to bridge the gap between specialised training and police performance. Specifically, this study attempts to examine the relationship between the specialised training, police performance and human-technology capability. It also determines the mediating effect of human-technology capability on the relationship between the specialised training and police performance. The real challenges and future directions of the Abu Dhabi Police Academy are also addressed in this study. A quantitative research approach was employed, utilizing a survey strategy designed to minimize bias and align with a positivist research model. Simple random sampling was used to collect primary data through face-to-face self-administered surveys and emailed questionnaires. Out of 355 questionnaires distributed, 336 valid responses were received, achieving a 94.7% response rate. The data were analyzed using SPSS and SmartPLS (PLS-SEM) with various statistical tools, including descriptive analysis, exploratory factor analysis, and reliability testing. The results indicate a significant relationship between specialised training, human-technology capability, and police officer performance. The findings show that both specialised training and human-technology capability positively impact officer performance, with human-technology capability serving as a mediator in this relationship. The qualitative interview data enriched the information on the opportunities, challenges and future strategies in integrating human-technology capability into police specialised training in Abu Dhabi. This study's significant contribution lies in its contextual relevance to Abu Dhabi, providing actionable recommendations for policymakers, police academies, and law enforcement agencies in the Emirati capital. This study would benefit the police force academies in Abu Dhabi, increasing the city's safety and effectively enhancing Abu Dhabi's economic growth.